Phytochemical analysis, analgesic and antipyretic properties of ethanolic leaf extract of Vernonia amygdalina Del. - Mustapha A Tijjani; Garba T Mohammed; Yagana T Alkali; Thiza B Adamu; Fanna I Abdurahaman (Shahrekord University of Medical Sciences, 2017)
Introduction: Vernonia amygdalina Del. has been traditionally used in relieving pain and inflammatory conditions as well as in treatment of feverish conditions by local people of the North-east Nigeria. Consequently this study aims at evaluating the phytochemical content, antipyretic and analgesic properties of V. amygdalina (biter leaf). Methods: The leaf of V. amygdalina was soxhlet extracted with ethanol and sequentially partitioned using solvent of different polarities. Phytochemical test was conducted to ascertain the secondary metabolites present in the extract using standard procedures. Acute toxicity (LD50) of the extract on laboratory rats was estimated by following protocols of Lorke. The antinociceptive activity of the ethanolic extract was also evaluated using acetic acid induced pain and hot plate method. Results: The results revealed the presence of tannins, phlobatannins, saponins, carbohydrates, cardioactive glycoside, flavonoids, alkaloids, steroids and terpenes. Anthraquinones were absent in the extract. The intraperitoneal LD50 was found to be 3721 mg/kg. On administration of 5000 mg/kg dose of the extract via oral route, there was no dead. The extract demonstrated significant antinociceptive activities as 36.0 ± 0.81, 43.8 ± 0.11 and 52.8±0.37 (Mean number of writhings) respectively for the doses 600, 400 and 200 mg/kg i.p.) as compared to the control (60.0 ± 0.11). High dose of 400 mg/kg significantly reduced rectal temperature (P < 0.05)Conclusion: These results demonstrated the medicinal potentiality of V. amygdalina and might be used as analgesic, and antipyretic agent. Phytochemicals found in such as flavonoids, tannins, alkaloids and steroids seem to be implicated in having such pharmacological activities.